ChemInform Abstract: Visible Light Driven Synthesis of 2‐Substituted Benzothiazoles Using CdS Nanosphere as Heterogenous Recyclable Catalyst. Issue 24 (23rd May 2013) - Das, Sudipto; Samanta, Suvendu; Maji, Swarup Kumar; Samanta, Partha Kumar; Dutta, Amit Kumar; Srivastava, Divesh N.; Adhikary, Bibhutosh; Biswas, Papu
Abstract The mesoporous CdS nanosphere is successfully applied in the preparation of various benzothiazole derivatives bearing aromatic, heteroaromatic or aliphatic residues at C‐2.